Associated factors of caregivers burden in dementia patient attending memory clinic in Hospital Pulau Pinang - Chai Nee, Ng (2015)
Background: Dementia is a chronic neurodegenerative disease characterized by memory impairment associated with loss of functional disabilities in the presence of consciousness. As the disease progresses, patient will become more dependent on their informal caregivers This study result showed that about 43% experiencing mild to moderate burden while caring for dementia patient. Objectives: This study was to determine the associated factors that contributed to the burden of care in our local settings. Methodology: A cross sectional study involving a total of 121 patients informal caregivers dyad which were recruited at memory clinic in Hospital Pulau Pinang. The outcome measure was Zarit Burden Interview and associated factors of burden were measured using Mini Mental Status Examination (MMSE), Disability Assessment of Dementia (DAD), Multidimensional Perceived Social Burden Scale (MPSS) and Malay Version Neuropsychiatry Inventory (MvNPI). Results: We managed to find an association between behavioral and psychological symptoms of dementia namely; delusion (p<0.001), apathy (p=0.052), wandering tendency (p=0.022), dyslipidemia (p<0.001), hours of caregiving (p=0.011) and perceived social support from significant others (p<0.001) associated with burden of care. Conclusion: Burden of care cannot be underestimate due to the risk of premature institutionalization and an increased in the health care cost. Therefore, early detection and prevention are mandatory to prevent deleterious effects on the caregiver.